Alimentação saudável no Brasil: certificação dos produtos orgânicos da agricultura familiar no marco do desenvolvimento sustentável - Favaretto, Felipe (2022)
With the purpose of contributing to the achievement of the Sustainable Development Goals of the 2030 Agenda in Brazil, this research aims to analyze how the certification of organic products from family farming, within the framework of sustainable development, can contribute to promoting healthy eating in the Brazil. For the development of this research, the work is concentrated in three chapters. The first chapter analyzes the foundations of the right to healthy food from sustainable production, considering the right to food as a fundamental social right, the characteristics of the normative evolution of the right to food in Brazil, as well as the analysis of the 2030 Agenda for Sustainable Development. In the second chapter, the work analyzes aspects related to the reality in the Brazilian countryside in terms of food (in)security and social exclusion, mainly observing the effect of the use of pesticides, which can affect food security, the concentration of income in rural areas and organic production in the field. The third chapter specifically examines the certification of organic products, taking into account the fundamentals of certification systems and organic certification programs, in particular the aspect related to sustainability of the organic product certification system in Brazil. The research highlights the potential of organic food production in promoting the 2030 Agenda, with a focus on sustainable agriculture and combating the social exclusion of family farmers. It was identified that technical and financial support is the main obstacle to the insertion and maintenance of farmers in the promising organic products market. Furthermore, there was a lack of accurate and updated information, which makes it impossible to have a more in-depth knowledge of the national organic production chain. The role of the State, through public policies, in promoting family farming stands out. Finally, the creation of a seal that identifies the social origin of the product, together with investment in consumer education, is a way of promoting sustainable agriculture and ensuring social maintenance in rural areas.